Use of soil correctives and the recovery of degraded pasture of Braquiaria brizantha (Research, Society and Development, 2021)
The raising of cattle in Brazil is one of the great pillars of the economy, in which every day the focus and greater availability of ideal food for consumption, generating better use of areas, thus increasing production per hectare. The objective of this work is to verify the efficiency of using soil correctives in the recovery of a degraded pasture. The experiment was carried out at Santa Barbara farm in the city of Orizona, Goiás, in a randomized block design, with three treatments of ten replications where the treatments were: control T1 without application of soil amendments; T2 – application of limestone 2.44 t ha-1; T3 - application of limestone 2.44 t ha-1 and agricultural gypsum 0.306 t ha-1. The planting of Brachiaria brizantha was carried out by broadcasting in the beginning of the rainy season with application of 10 kg ha-1, after 90 days of planting the material was collected. Forage collections were carried out with the aid of an iron square with a diameter of 1.0 m2, being released under the pasture area in 10 random points within each treatment. The contents of dry matter, crude protein, moisture, ether extract, crude fiber, mineral material, Ca%, P%, NDT% were evaluated. The work showed a positive result in the use of correctives (limestone + gypsum) with an increase of 21% greater production of dry matter and levels of macronutrients suitable for animal feed.